Species abundances above the lysocline over the last ~40 ka measured in sediment core SSD044_GC01 from the equatorial Indian Ocean - Ramanand Yadav; Sushant S Naik; Pothuri Divakar Naidu (PANGAEA, 2022)
In this data set, we present percentage of calcium carbonate (CaCO3), ratio of organic carbon to total nitrogen, coarse fraction (>63 μm), size index percentage, total planktic foraminifera number, foraminifera fragment percentage (>125 μm), the ratio of benthic to planktic foraminifera, Globorotalia spp. percentage and Radiolarian percentage as well as the planktic foraminifera assemblage to show the carbonate dissolution in the deep sea region of the central Equatorial Indian Ocean (5°N & 77°E) over the last 40 ka. The marine sediment core SSD044_GC-01 was collected during the 044th Cruise of Research Vessel Sindhu (SSD044) Sadhana using a Gravity corer. To analyze the species abundance of planktic foraminifera, a portion of the Coarse Fraction (>63 μm) was dry sieved from 125 μm size fractions. Approximately ~300 intact tests of planktic foraminifera were picked and dissolution-sensitive and insensitive species abundance were made to show a carbonate ion concentration in the deep sea region of the study area during the last 43ka.